2010
DOI: 10.1007/s11517-010-0707-x
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex analysis in diabetes mellitus: linear and nonlinear approaches

Abstract: The aim of our study was to employ novel nonlinear synchronization approaches as a tool to detect baroreflex impairment in young patients with subclinical autonomic dysfunction in Type 1 diabetes mellitus (DM) and compare them to standard linear baroreflex sensitivity (BRS) methods. We recorded beat-to-beat pulse interval (PI) and systolic blood pressure (SBP) in 14 DM patients and 14 matched healthy controls. We computed the information domain synchronization index (IDSI), cross-multiscale entropy, joint symb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 37 publications
1
27
0
1
Order By: Relevance
“…Since high circulating NPY was found in patients suffering from diabetes, hypertension as well as cardiac disease [8,11,13,14], and baroreflex sensitivity was severely impaired in patients with diabetes or hypertension [1,27,28], we speculate that NPY may participate in this process. Though previous studies have reported that central and intravenous injections of NPY led to changes in the ABP and HR [20,29], the chronic effect of NPY on baroreflex sensitivity has not yet been clarified under disease status.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Since high circulating NPY was found in patients suffering from diabetes, hypertension as well as cardiac disease [8,11,13,14], and baroreflex sensitivity was severely impaired in patients with diabetes or hypertension [1,27,28], we speculate that NPY may participate in this process. Though previous studies have reported that central and intravenous injections of NPY led to changes in the ABP and HR [20,29], the chronic effect of NPY on baroreflex sensitivity has not yet been clarified under disease status.…”
Section: Discussionmentioning
confidence: 90%
“…Impaired baroreflex control of heart rate (HR), as an indicator of abnormal baroreflex sensitivity, is closely related to life-threatening arrhythmias, heart failure and sudden death induced by various diseases, such as cardiac ischemia, diabetes, hypertension, and even depression [1][2][3][4]. Within the baroreflex circuitry, both sympathetic and 112 parasympathetic nervous systems contribute to the regulation of heart function, and the nucleus tractus solitarii (NTS) and nucleus ambiguous (NA) in the brainstem have been considered as the central domain participating in baroreceptor reflex [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Javorka et al (Javorka, Lazarova et al 2011) compared heart rate and blood pressure variability among young patients with type I diabetes mellitus (DM) and control subjects by using Poincare plots, which are the standard tools of nonlinear dynamic analysis. They found significant reduction of all HRV Poincare plot measure in patients with type I diabetes mellitus, indicating heart rate dysregulation.…”
Section: A Novel Technique For Identifying Patients With Icu Needs Usmentioning
confidence: 99%
“…The Poincare plot is a graph in which each heart rate episode is plotted as a function of previous HR, and then the line y=x is fitted to the data. In (Javorka, Lazarova et al 2011) this method is also applied to classify patients with type I DM from healthy subjects. Drawing the Poincare plot for healthy and abnormal subjects, it is found that the deviation from the mentioned line in healthy subjects is less than in abnormal subjects.…”
Section: Poincare Plot Deviationmentioning
confidence: 99%